Vaccination Hesitancy in Parents with Children Aged under Five Years who Apply to a Family Health Centre - Bulut, Aliye; Atıcı, Erhan (Yuzuncu Yil Universitesi Tip Fakultesi, 2024)
Introduction: This study aimed to determine the factors that cause vaccine hesitancy in parents with children under five years of age who applied to a family health center, to examine parents’ behaviors and their motives for vaccine hesitancy, and to make recomme ndations for parents in their decisions regarding their childhood vaccines. Materials and Methods: The researcher collected the data from parents who applied to two Family Health Centers in the city center of Elazığ for several reasons: were over 18 years of age, agreed to participate in the study, and had children under the age of five (n= 123). An Individual Information Form prepared by the researchers based on the literature and the Vaccine Hesitancy Questionnaire, a nd the Vaccine Hesitancy Scale (VHS) developed by the World Health Organization Strategic Advisory Group of Experts Working Group on Vaccine Hesitancy. Results: Despite no statistically significant difference in this study, it was found that those who were aged between 19 and 25 years, had a son, were fathers, were married, had employed mothers, and had unemployed fathers had higher mean ranks of VHS. The VHS scores of those with low educational levels in mothers and fathers who had low educational levels were unaware of how their spouses fel t about vaccination and reported that they had been informed negatively about vaccination differed from each other. Conclusion: The parents are hesitant about the vaccination of their children for several reasons. Families who hesitate to vaccinate thei r children should be fought socially, and their awareness should be raised. © 2024, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: children under five; parents; Vaccination; vaccine hesitancy